PERAN APARAT PENGAWASAN INTERNAL PEMERINTAH DALAM PENCEGAHAN KECURANGAN PENGELOLAAN DANA DESA DI KABUPATEN NGAWI - Berliana, Nadila; Purbasari, Heppy (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Village funds are defined as funds sourced from the APBN earmarked for villages that will be transferred through the Regency/Municipal APBD and used to finance government administration, development implementation, community development, and community empowerment. The research aims to find out and analyze the role of APIP supervision in preventing village fund management fraud in Ngawi district, whether it is following the Minister of Home Affairs Regulation Number 73 of 2020. This research used qualitative descriptive research by interviewing 5 ( five) auditors at the Ngawi District Inspectorate. The study results showed that the Ngawi district inspectorate followed Permendagri No. 73 of 2020. The obstacle faced by the inspectorate was the lack of auditors and village officials who did not understand the importance of transparency in the financial management of village funds. The Ngawi District Inspectorate in conducting guidance and supervision complies with existing regulations and has provided maximum performance in terms of the quantity and quality of its human resources.